Therapeutic effects of Vernonia amygdalina on the expression of hormone and HER2 receptors in 7, 12-dimethylbenz(a)anthracene-induced breast tumours in obese and non-obese Wistar rats - Adeleye Dorcas Omisore; Adeleke Adegboyega Abiodun; David Olawale Adeyemi; Ayodeji Zabdiel Abijo; Kehinde Akinyemi Jolayemi; Akinola Ayodeji Odedeyi (Elsevier, 2022)
Background: Obesity, a risk factor for breast cancer has been shown to be associated with poor response to neoadjuvant chemotherapy in women with breast cancer. Medicinal plants have been used to treat chronic diseases like cancer with little or no side effects. Vernonia amygdalina (VA) is a medicinal plant with anticancer activity. Previous studies on the anticancer potential of V. amygdalina against breast cancer are however entirely in vitro studies. The efficacy of V. amygdalina on obesity-associated breast cancer has also not been investigated in previous studies. This study explored VA's anti-cancer effects on obesity- and non-obesity-associated 7,12-dimethylbenz(a)anthracene (DMBA)-induced breast tumours in Wistar rats (WRs). Method: Thirty female obese and non-obese WRs were studied, each group divided into six subgroups of five. At the 7th postnatal week (p.w), three subgroups were given a subcutaneous injection of DMBA to the breast with two of these three subgroups also commenced on daily oral VA at 250 mg/kg and 500 mg/kg from the 9th p.w. Same doses of VA were administered to two of the subgroups that did not receive DMBA while the last subgroup was placed on placebo from the 9th p.w. Haematoxylin and eosin staining were carried out on the excised breast tumours to evaluate general histoarchitecture, while immunohistochemistry was done for oestrogen (ER), progesterone (PR), and human epidermal growth factor receptor 2 (HER2) expression. ANOVA and Mann-Whitney followed by posthoc tests were used to analyse the data. Alpha level was set at 0.05. Results: While the DMBA-induced tumours were triple-negative in the obese WRs, they were ER, PR HER2-positive in the non-obese group. Vernonia amygdalina was associated with a reduction in cancer cell proliferation in both obese and non-obese groups despite the differences in immunohistochemical profiles of the tumours. Vernonia amygdalina was associated with reversal of the increased ER, PR and HER2 expressions in the breast tumours of the non-obese rats. Conclusions: Conclusively, VA had more therapeutic effects on DMBA-induced breast tumours in the non-obese than obese WRs.